Síntese hidrotérmica e caracterização estrutural de titanatos nanotubulares para aplicação na captura do dióxido de carbono - Silva, Edjane Fabiula Buriti da (2012)
Nanostructured materials have been spreading successfully over past years due its size and unusual properties, resulting in an exponential growth of research activities devoted to nanoscience and nanotechnology, which has stimulated the search for different methods to control main properties of nanomaterials and make them suitable for applications with high added value. In the late 90 s an alternative and low cost method was proposed from alkaline hydrothermal synthesis of nanotubes. Based on this context, the objective of this work was to prepare different materials based on TiO2 anatase using hydrothermal synthesis method proposed by Kasuga and submit them to an acid wash treatment, in order to check the structural behavior of final samples. They were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), adsorption/desorption of N2, thermal analysis (TG/DTA) and various spectroscopic methods such as absorption spectroscopy in the infrared (FT-IR), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). All the information of characterizations confirmed the complete conversion of anatase TiO2 in nanotubes titanates (TTNT). Observing the influence of acid washing treatment in titanates structure, it was concluded that the nanotubes are formed during heat treatment, the sample which was not subjected to this process also achieved a complete phase transformation, as showed in crystallography and morphology results, however the surface area of them practically doubled after the acid washing. By spectroscopy was performed a discussion about chemical composition of these titanates, obtaining relevant results. Finally, it was observed that the products obtained in this work are potential materials for various applications in adsorption, catalysis and photocatalysis, showing great promise in CO2 capture